Validity of the ideological left/right continuum during 2011 Presidential Elections in Lima-Peru - Rottenbacher, Jan Marc (2012)
This study analyzes the relationship between political ideology, voting behavior and emotional responses after Peruvian presidential elections in 2011. Scales of intolerance for ambiguity, need for closure, right-wing authoritarianism (RWA) and the right-wing political orientation were used to assess right-wing political conservatism. A structural equation model proposes that intolerance of ambiguity and need for closure exert a direct effect on RWA. Also, RWA influences directly the right-wing political orientation, which exerts a direct influence on negative emotional responses and an inverse effect on positive emotional responses after O. Humala’s victory. Final discussion focuses on the contemporary relevance of left/right ideological continuum.